Analysis of Decision Making of Energy Enterprises on Adaptive Behavior Amid COVID-19 - Yang, Xiurui; Li, Jizu (Frontiers in Energy Research, 2021)
There is no choice for energy businesses with ongoing epidemic prevention and control but to adapt themselves to the epidemic. Analyzing the decisions of energy enterprises on adaptive behaviors amid the Corona Virus Disease 2019 (COVID-19) pandemic goes a long way towards economic and social stability and successful containment of the pandemic. With a phone-based or online (Tencent QQ and WeChat) survey on 500 energy companies in 17 prefecture-level cities and autonomous prefectures in Central China’s Hubei Province, we examined the types of adaptive behavior these businesses had chosen to respond to the virus. We utilized the entropy weight method (EWM) and identified key factors that impacted how these companies made decisions on adaptive behavior. On that basis, we compared the samples with state-owned enterprises and private businesses in terms of the criticality of factors affecting their decisions on adaptive behavior. The significant findings are as follows. First, the adaptive behaviors of Hubei-based energy companies were for philanthropic, economic, or technical purposes. Besides, concerning the confidence level, the central government’s general requirement for epidemic prevention and control, current economic realities, cost-benefit analysis of adaptive behavior, the awareness of corporate social responsibility, and energy policy support from governments were key factors that affect decisions of Hubei’s energy enterprises on adaptive behavior. Their criticality rates 0.999 6, 0.999 5, 0.999 0, 0.997 1, and 0.995 8, respectively. Moreover, the key affecting factors of these samples differed from those of energy enterprises of a different nature. The nature of energy businesses holds sway over the identification of those key factors. The criticality of which also varies with the distinctive nature of the enterprises. Finally, we presented the theoretical implications of the present work and policy-making recommendations.